The Effect of Company Growth, Company Size, Dividend Policy, and Capital Structure on The Value of Companies in Manufacturing Companies Listed on The Indonesia Stock Exchange for The Period of 2020-2023 - Fransiska Destiana Solo; Mukoffi, Ahmad; Hidayat, Imam (International Research & Development for Human Beings (IRDH), 2025)
Using secondary data from annual financial reports and Price to Book Value (PBV) as a measure of firm value, this study examines how firm size, business growth, dividend policy, and capital structure affect the value of manufacturing businesses listed on the IDX between 2020 and 2023. The results of the multiple linear regression analysis of this study indicate that firm growth has no significant impact on its value. On the contrary, the scale of the company significantly increases its value. The study's findings yield a number of important conclusions. First, the company's expansion does not have much effect on the value of manufacturing companies listed on the IDX. Second, it is clear that the size of a company affects its value, with larger companies often having higher values. Furthermore, there is no clear impact of the dividend policy on the company's valuation, which suggests that investors are more concerned with other considerations.